2014
DOI: 10.5688/ajpe78473
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health Sciences Reasoning Test Scores With Academic and Experiential Performance

Abstract: Objectives. To assess the association of scores on the Health Sciences Reasoning Test (HSRT) with academic and experiential performance in a doctor of pharmacy (PharmD) curriculum. Methods. The HSRT was administered to 329 first-year (P1) PharmD students. Performance on the HSRT and its subscales was compared with academic performance in 29 courses throughout the curriculum and with performance in advanced pharmacy practice experiences (APPEs). Results. Significant positive correlations were found between cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…11,12 Grades will not likely be highly linked to or predictive of critical thinking unless a course is explicitly designed to teach and assess critical thinking. Job performance, positive decision making, leadership abilities, implementation of evidenced-based-medicine, job retention, creativity in problem solving, and many other positive qualities are strongly and positively correlated with critical thinking, unlike grades, SAT scores, and class rank.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Grades will not likely be highly linked to or predictive of critical thinking unless a course is explicitly designed to teach and assess critical thinking. Job performance, positive decision making, leadership abilities, implementation of evidenced-based-medicine, job retention, creativity in problem solving, and many other positive qualities are strongly and positively correlated with critical thinking, unlike grades, SAT scores, and class rank.…”
Section: Discussionmentioning
confidence: 99%
“…Job performance, positive decision making, leadership abilities, implementation of evidenced-based-medicine, job retention, creativity in problem solving, and many other positive qualities are strongly and positively correlated with critical thinking, unlike grades, SAT scores, and class rank. [12][13][14][15][16] Individuals who test highly in critical-thinking are less likely to display problem behaviors or make biased decisions. 16 These less tangible aspects of any professional practice are linked with one's ability to think critically, so the HSRT would be better than grades or academic performance at predicting these measures of success.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying and measuring applicant attributes indicative of student pharmacist success is a complex undertaking. [28][29][30] Limitations associated with rater bias and context specificity, for example, can challenge the identification and measurement of these attributes at the point of admissions. While the findings of this study suggest the MMI provides valid and reliable information about noncognitive attributes, several limitations are worth noting.…”
Section: Discussionmentioning
confidence: 99%
“…7,23 Similarly, tools designed to assess clinically relevant competencies, such as the Health Professions Admission Test and Health Sciences Reasoning Test, tend to be weakly correlated with OSCEs and/or clinical practice experience performance. 8,24,25 During the admissions process, schools should consider more reliable and effective practices for assessing noncognitive and professional skills considered vital to success as a practitioner. 22,[26][27][28] Although several studies have reported correlations between grades in the didactic curriculum of pharmacy schools with uGPA and PCAT scores, 11,29,30 strategies for predicting a student's potential to be successful in clinical settings warrant further attention and development.…”
Section: Discussionmentioning
confidence: 99%
“…However, a growing body of literature demonstrates the challenges associated with predicting an applicant's future performance. [8][9][10] Previous studies suggest that prepharmacy academic indicators, such as undergraduate grade point average (uGPA) and Pharmacy College Admission Test (PCAT) scores can be predictive of performance in didactic coursework. However, the strength of these relationships tends to decrease for each subsequent year of the program.…”
Section: Introductionmentioning
confidence: 99%